Topological bi-K-equivalence of pairs of map germs - Birbrair, Lev; Costa, João Carlos Ferreira [UNESP]; Filho, Da Silva Sena (Department of Mathematics, Hokkaido University, 2018)
Let Pk(n, p × q) be the set of all pairs of real polynomial map germs (f, g): (ℝn; 0) → (ℝp × ℝq; 0) with degree of f1, . . ., fp, g1, . . ., gq less than or equal to k 2 N. The main result of this paper shows that the set of equivalence classes of Pk(n, p × q), with respect to bi-C0-K-equivalence, is finite.
Keywords: Finiteness theorem; Pairs of map germs; Topological classification; Topological contact equivalence